Screening of maize (Zea mays L.) lines using selection indices for salinity stress tolerance - Sorour Arzhang; Reza Darvishzadeh; Hadi Alipour (تنش های محیطی در علوم زراعی, 2023)
IntroductionSalinity stress is one of the main abiotic stress factors and environmental problems affecting crop yields worldwide, especially in arid and semi-arid regions. Land salinization is increasing, with 10 million ha of agricultural land destroyed annually. An increase in the concentration of salts in soil solution or irrigation water adversely affects plant growth and productivity, which can substantially reduce yield production. Maize (Zea mays L.) is the third most important cereal grain after rice and wheat, due to its high yield and nutritive value and also known as the queen of cereal crops and is moderately sensitive to salinity stress. Accurate screening of maize tolerant genotypes using selection indices for salinity stress tolerance is an efficient approach to improve salinity tolerant crop plant genotypes, as well as reduce the effect of salinity on this crop.Materials and methodsThis study was conducted at the Urmia University Research Farm in 2017 to evaluate the influence of salinity stress (8 dSm-1) on the grain yield of 86 maize lines, as well as identify salt-tolerant maize lines based on selection indices for salinity stress tolerance. The pot experiments in normal and salinity stress conditions were set up in a randomized complete block design (RCBD) with three replicates. Ten selection indices for salinity stress tolerance including Stress Susceptibility Index (SSI), Tolerance Index (TOL), Stress Tolerance Index (STI), Mean Productivity (MP), Geometric Mean Productivity (GMP), Harmonic Mean (HM), Abiotic Tolerance Index (ATI), Drought resistance Index (DI), Modified Stress Tolerance Index in normal condition (MpSTI), and Modified Stress Tolerance Index in stress condition (MsSTI) were calculated based on grain yield of lines under normal and salinity stress conditions.Results and discussionA wide range of genetic variability was obtained among the studied maize lines in terms of grain yield under normal and salinity stress conditions as well as in terms of selection indices for salinity stress tolerance, which provided suitable conditions for evaluating tolerance indices and selection of tolerant lines. STI, MP, GMP, and HM had the highest correlation with grain yield in both normal and salinity stress conditions and were suitable to screen salt-tolerant and high-yielding maize lines. The three-dimensional (3D) plot obtained from these indices showed that the lines Ma025, Ma010, Ma026, Ma011, Ma009 Ma015, Ma116, Ma012, Ma028, and Ma062, which were in group A, had high yields in both normal and stress conditions. The results obtained from the use of principal component analysis showed that the first two principal components account for 93% of the total variance. The first component, called yield potential, had a very significant correlation with STI, MP, GMP, HM, DI, MpSTI, and MsSTI and was able to separate high-yielding maize lines in both normal and stress conditions. The second component, called sensitive or tolerant to salinity stress, had a very high correlation with SSI, TOL, and ATI and was able to distinguish stable maize lines. According to the hierarchical cluster analysis, a total of 86 maize lines were grouped in three tolerant, semi-tolerant, and sensitive clusters somehow this clustering was completely consistent with the separation of maize lines by the first principal component. In addition, each of these clusters had two subclusters that were separated according to the second principal component, so that in each cluster, the lines that had high yield stability were placed in the first subcluster, and the lines that had lower yield stability were placed in the second subcluster. Thus, Ma010, Ma026, Ma009, Ma027, Ma023, Ma007, and Ma005 were introduced as salt-tolerant maize lines with stable yields to use in breeding programs.ConclusionBased on the available findings, the present study, as the first study on a large number of maize lines (86 lines) in the country, evaluated salinity stress tolerance using selection indices. The results of this study revealed the importance of using selection indices for stress tolerance as a reliable and useful tool to improve salinity stress tolerance in maize lines. Accordingly, STI, MP, GMP, and HM were identified as the most appropriate indices for the selection of tolerant and stable maize lines using multivariate statistical methods. It is recommended that the selected maize lines be considered as parent lines in future breeding programs in order to improve salinity stress tolerance and stable grain yield.